Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline

Organocatalytic enantioselective approach to the synthesis of verbalactone and (R)-massoialactone - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
The organocatalytic enantioselective synthesis of verbalactone and (R)-massoialactone is described. The requisite stereogenic centers of the target molecules were constructed using L-proline-catalyzed alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination. Yamaguchi macrolactonization and ring-closing metathesis were employed as key steps in the syntheses.
Keywords: alpha-aminoxylation; Horner-Wadsworth-Emmons olefination; L-proline; massoialactone; Ring-closing metathesis; verbalactone; Yamaguchi macrolactonization

Organocatalytic route to the synthesis of (6S)-5,6-dihydro-6-[(2R)-2-hydroxy-6-phenylhexyl]-2H-pyran-2-one and ravensara lactones - Dwivedi, Namrata; Tripathi, Divya; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An organocatalytic enantioselective synthesis of the title compounds has been achieved. The stereogenic centers were generated by the iterative use of proline catalyzed alpha-aminoxylations and HWE olefination of aldehydes while the lactone ring was constructed by ring closing metathesis. (C) 2011 Elsevier Ltd. All rights reserved.

Organocatalytic stereoselective synthesis of passifloricin A - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2012)
The enantioselective synthesis of passifloricin A has been achieved in high diastereomeric excess. The 1,3-polyol moiety was constructed by iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes while the synthesis of lactone moiety was achieved by ring-closing metathesis (RCM).

Organocatalytic stereoselective approach to the total synthesis of (-)-halosaline - Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2014)
A practical and efficient organocatalytic approach to the synthesis of substituted piperidine alkaloids in high enantio- and diastereomeric excess was achieved using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and HWE olefination reaction of an aldehyde.

Organocatalytic route to the enantioselective synthesis of syn/ anti-α-hydrazino-γ-fluoro alcohols - Khonde, Nilesh S.; Said, Madhukar S.; Danve, Shivam S.; Kumar, Pradeep (Tetrahedron Letters, 2024)
A general organocatalytic method has been developed for the asymmetric synthesis of alpha-hydrazino-gamma-fluoro alcohols, a precursor to syn/anti-1,3-fluoro amines. The strategy employs alpha-fluorination catalyzed by prolinederived catalyst, (S)-alpha,alpha-bis[3,5-bis(trifluoromethyl)phenyl]-2-pyrrolidinemetha nol trimethylsilyl ether followed by Horner-Wadsworth-Emmons (HWE) olefination of aldehydes, and proline-catalyzed alpha-amination as the key steps. The title compounds showed excellent diastereoselectivity (up to 99:1) and enantioselectivity (up to 99 %).
Keywords: alpha-Amination; alpha-Fluorination; diastereoselectivity; Enantioselectivity; HWE olefination; organocatalyst